Estimating Endogenous Dopamine Levels at D(2) and D(3) Receptors in Humans using the Agonist Radiotracer [(11)C]-(+)-PHNO - Caravaggio, Fernando (Nature Publishing Group, 2014)
Using positron emission tomography (PET) and an acute dopamine depletion challenge it is possible to estimate endogenous dopamine levels occupying dopamine D(2/3) receptors (D(2/3)R) in humans in vivo. Our group has developed [(11)C]-(+)-PHNO, the first agonist radiotracer with preferential in vivo affinity for D(3)R. Thus, the use of [(11)C]-(+)-PHNO offers the novel possibility of (i) estimating in vivo endogenous dopamine levels at D(2/3)R using an agonist radiotracer, and (ii) estimating endogenous dopamine levels at D(3)R in extrastriatal regions such as the substantia nigra, hypothalamus, and ventral pallidum. Ten healthy participants underwent a [(11)C]-(+)-PHNO PET scan under baseline conditions and another under acute endogenous dopamine depletion achieved via oral administration of alpha-methyl-para-tyrosine (64 mg/kg). [(11)C]-(+)-PHNO binding was sensitive to acute dopamine depletion, allowing in vivo estimates of endogenous dopamine in D(2)R-rich regions (caudate and putamen), mixed D(2/3)R-rich regions (ventral striatum and globus pallidus), and extrastriatal D(3)R-rich regions (hypothalamus and ventral pallidum). Dopamine depletion decreased self-reported vigor, which was correlated with the reduction in dopamine levels in the globus pallidus. [(11)C]-(+)-PHNO is a suitable radiotracer for use in estimating endogenous dopamine levels at D(2)R and D(3)R in neuropsychiatric populations.